CONTESTATION BETWEEN STATE AND NONSTATE ACTORS IN ZAKAH MANAGEMENT IN INDONESIA - Susetyo, Heru (Jurnal Syariah, 2017)
This paper is aimed to study the contestation between state and civil society in zakah management in Indonesia as a part of socio political dynamic of secularization of zakah as an Islamic economy instrument in Indonesian situation. More specifically, about how the state of Indonesia manages to secularize the zakah as a divine instrument into a country which adopt semi-secular system. The research scrutinizes the contestation between state and civil society in zakah management through the cases and trial observation at Indonesian Constitutional Court (on judicial review the Law No. 23/2011 on Zakat Management) and Supreme Court (judicial review Government Regulation No. 14/2014 on Zakat Management). Some resistances to local ordinances on zakah management in various places in Indonesia are also being studied. The research has shown that the practice of zakah in Indonesia is specific and different from the practices in other Muslim countries. In a predominantly Muslim country, zakah practices in Indonesia are actually a product of Indonesian Muslims’ social, cultural, and political dynamics. The research employs Joel S. Migdal theory on contestation. In these Migdalian’s “junctures” between state forces and social forces, these non-state zakah agencies naturally launch contestation in both forms of struggle and accommodation. These non-state agencies accommodate their survival through modernization of their daily operation to reach more sources of funds and targets as well as launch a legal struggle to annul some disadvantageous parts within the newly arrived secularization of zakah management through the politicization of zakah. In the meeting grounds for state and social forces, the results vacillate - depending on the place and context of the contestation - between what Migdal (1994) calls the state’s appropriation of social forces or symbols and the dominant social forces’ adaptation to the presence of a state’s components. In this set of mutual accommodation strategies, all become possible: co-optation, creation of multiple networks of clients, and corruption.